A Delphi study on thematic interpretations of al-Qur’ān - Salahuddin, Ashraf Ali; Othman, Roslina (Institute of Electrical and Electronics Engineers Inc., 2018)
Thematic interpretations of al-Qur’ān (TIaQ) or Tafseer al-maudu’iy ( )- has a sensitivity due to the interrelation of Qur’ānic verses with each other. The purpose of this research was to extract the online Qur’ānic search engines (OQSE) and investigate the existing thematic interpretations of al-Qur’ān (TIaQ) based on the alignment with their relevant verses. The OQSEs provide the list of themes and the aligned verses in their websites. The ambiguous thematic search engines have the possibility to mislead the user by retrieving nonaligned verses against a certain subject/theme (query) or the user may not fully understand the interpretations due to the incomplete results. However, this research has underlined a two stages research design to investigate the existing TIaQ in OQSE. The extracting of themes and aligned verses have been done using Cranfield’s Index Device method and a two-round Delphi method has been applied to justify the existing themes and the aligned verses by 20 experts of Qur’ānic discipline. There are 240 themes and 400 verses have been extracted and categorized into 40 thematic groups (TG). The experts’ justification through Delphi method has revealed that the accuracy of ordinated thematic groups in OQSE is 40% (16/40) only and the accuracy of the ordination of themes and verses achieved 35.41% (85/240). Despite the significant outcome of this research, the limitation recommends that the further research should be conducted extracting more themes and aligned verses from OQSEs. Instead of 20 experts in Delphi, future research can concentrate on a big number of experts to investigate all the thematic verses of entire Qur’ān. © 2018 IEEE.